Assessment of heavy metal residues in water, fish tissue and human blood from Ubeji, Warri, Delta State Nigeria (2013)
Residual levels of lead, chromium, cadmium and zinc in water and fish tissue from Ubeji River, Warri and blood samples from residents of Ubeji were analysed. Control water and fish samples were obtained from Eleyele River and blood from residents of Ibadan. All the samples collected were digested using a modified procedure from the Association of Official Analytical Chemists (AOAC) and were subsequently analyzed using Atomic Absorption Spectroscopy. Levels of lead and cadmium in Ubeji river were significantly higher than levels in Eleyele River. Fifty fish samples from five species (Citharinus citharus, Liza falcipinis, Brycinus macrolepidotus, Polydactylus quadrifilis and Tilapia zilli) were analysed. Lead concentration (ppm) was highest in C. citharus (76.07±161.48) and least in T. zilli (23.16±26.30). Chromium was not detected in B. macrolepidotus, P. quadrifilis and T. zilli. Concentrations of all heavy metals detected, except zinc, in the fish species were higher than WHO permissible limit. Lead, Cadmium and Zinc concentrations in the tissues of then control fish were significantly lower (p>0.05) than those recorded in fish from Ubeji River. There were no statistically significant differences in heavy metal concentration in fish gills and muscle (p>0.05). Lead and cadmium levels in Ubeji river significantly exceeded (p=0.0 and p=0.012) the permissible limits for aquaculture and drinking. Levels of Chromium (1737.17±2996.01), Zinc and Lead (149.35±188.28 and 123.49±350.85 respectively) were significantly high (p<0.05) in the 101 human blood samples screened, while concentrations of Cadmium was comparatively low (10.11±10.71). Lower levels of cadmium, zinc and lead (8.54± 7.49, 79.89±62.65 and 53.46±57.17, respectively) were recorded for the control samples from Ibadan. This study highlights the high levels of heavy metals in the Ubeji River and suggests the need for interventions to stem the tide of pollution in the river. It would also be important to assess health problems that may arise as a result of contact and continuous use of the water.